An assessment of knowledge, attitudes and practices on pureed diet preparation (KAP DYS-PUREE) among food handlers in Malaysian hospitals for dysphagia management - Aizul Azri Azizan; Suzana Shahar; Zahara Abdul Manaf; Hasnah Haron; Nurul Fatin Malek Rivan; Nurul Huda Razali (Multidisciplinary Digital Publishing Institute, 2024)
This study aims to assess the knowledge, attitude, and practice towards pureed diet preparation among food handlers using a newly developed questionnaire for dysphagia management. A descriptive cross-sectional design study with purposive sampling was conducted in three government hospitals in the Klang Valley, Malaysia. A newly developed questionnaire, comprised of 40 quantitative items, was used and distributed to 161 food handlers from three hospitals who were directly involved in preparing pureed diets. The results demonstrated a low to moderate knowledge score among food handlers (57.54 ± 12.33), with scoring at 1.95% (very low), 28.6% (low), and 68.3% (moderate). Only 1.2% scored well in the knowledge section on pureed diet preparation. The attitude among food handlers showed that they were referred to the right source of reference before preparing the pureed diet (3.97 ± 1.35). The findings also clearly showed that the practice of using the right equipment (4.41 ± 1.19) is essential for pureed diet preparation. In conclusion, this study serves as a prognosis for future improvement in knowledge, attitude, and practice among food handlers toward pureed diet preparation. Knowledge among food handlers needs to be enhanced, and a comprehensive guideline and reference module will aid in refining dysphagia management, specifically in food preparation by food handlers.